Successful use of tocilizumab in the treatment of multisystem inflammatory disease of childhood refractory to intravenous immunoglobulin and glucocorticoids - Jitendra S Oswal; Bhakti Sarangi; Guruprasad Hassan Shankar; Varsha Sharma (Wolters Kluwer Medknow Publications, 2021)
Multisystem inflammatory syndrome in children (MIS-C) is one of the many challenges thrown by the ongoing SARS CoV-2 pandemic. A high index of suspicion is warranted for the diagnosis of MIS-C as presenting features overlap with Kawasaki disease and toxic shock syndrome. The treatment guidance is empirical with consideration of intravenous immunoglobulin (IVIG) and glucocorticoids. However, treatment of refractory MIS-C remains eluded. We describe here a 7-year-old boy with MIS-C refractory to IVIG and pulse methylprednisolone who responded to interleukin-6 inhibition using tocilizumab.